On a solution to improve the object detection ability of radars by dynamic polarization method - Nguyen Quoc An (ASEAN Journal on Science and Technology for Development, 2006)
One of the most importan problems of modern radar is increasing object detection, object distinction ability. In the last years, the used traditional radar signal processing methods are seem to use up. For solving this question, specialists are interested in analyzing the fine structure of radar signal, and the first is po larization structure. The use of polarization information allows to raise the information ability of radar systems and provides high probability of radar objects detection, high contrast of small-scale man-made objects on the radar map and radar objects classification.The article deals with the detection of radar objects by exploiting the information on polarization based on the scattering matrix (SM) of the object. A solution to improve the object detection ability of radars by dynamic polarization method (to modify the polarization of radiative wave) is introduced.